M20 Early outcomes of lung cancer referrals from the liverpool healthy lung project, a community based targeted lung cancer screening pilot. (December 2018) - Mason, S; Fidoe, D; Hill, S; Frost, F; Ledson, MJ; Field, JK
Abstract : Introduction: Liverpool has one of the highest rates of lung cancer incidence and mortality in England. In response, the Liverpool Healthy Lung Project (LHLP), a co-ordinated public engagement programme has begun offering low dose CT scans to populations with high lung cancer risk. Suspected lung cancers are referred to one of two lung cancer MDTs (Liverpool and Aintree) in the region. Here, we investigated the yields and outcomes of subsequent referrals to the Liverpool Lung Cancer MDT. Methods: Case-note review was undertaken for all participants referred to the Liverpool Lung Cancer MDT via the LHLP, up until February 2018. Baseline demographics, subsequent investigations, diagnosis, management and outcomes were recorded. Results: 34 referrals were made to the Liverpool Lung Cancer MDT. A subsequent diagnosis of lung cancer was made in 18/34 (52.9%) cases (16 NSCLC, 1 small cell, 1 carcinoid) and 13/18 (72.2%) were stage I-II. 14/18 (77.8%) lung cancers underwent resection which is >3 times higher than the local resection rate with no benign resections. Of those without a lung cancer diagnosis 10/16 (62.5%) underwent a PET scan and 4/16 (25%) underwent invasive diagnostic procedures, (CT-guided biopsy=2 and EBUS=2) which found one thymoma requiring surgery, one sarcoidosis and two inflammatory lesions. 14/16 (87.5%) remain under CT follow-up. Conclusions: The Liverpool Healthy Lung Project identifies early stage lung cancers with a subsequent high resection rate. Importantly, there were no non-malignant resections and in those found not to have cancer, few invasive procedures were performed and hence this approach appears to be associated with minimal harm.